Instilling hope for a brighter future: A mixed‐method mentoring support programme for individuals with and recovered from anorexia nervosa. Issue 5 (11th January 2018) - Ramjan, Lucie M.; Fogarty, Sarah; Nicholls, Daniel; Hay, Phillipa
Abstract : Aims and Objectives: To investigate the feasibility of a 13‐week mentoring programme in providing social support to promote hope for recovery in anorexia nervosa. Background: With no clear first‐line psychological treatment for people with anorexia nervosa, mentoring support programmes, as an adjunct to treatment, may provide the social support necessary to promote hope for recovery. Design: A mixed‐method study; participatory action research. Methods: Women ( n  =   11), recovering and who had recovered from anorexia nervosa, participated in the programme and completed self‐report questionnaires related to quality of life, distress and the mentoring relationship at different time points. Qualitative feedback from logbooks, workshop evaluation questionnaires, interviews and focus groups was also collected to assess the programme's acceptability. Results: General compliance for completing most study outcome questionnaires was 90%; however, the mentoring relationship questionnaires were not completed to the same degree. Five key themes emerged from the focus group/interview data: (i) she understands me and could relate to me; (ii) reconnecting with the world—asking questions and being challenged; (iii) mentors' altruistic motivations and the transformation and discovery of self; (iv) instilling hope—recovery is possible; and (v) effective communication—the key to successful mentoring. Conclusions: Further research is needed; however, the results provide preliminary support for the mentoring programme's feasibility as an adjunct to treatment. We found that having someone who understands, to talk and share with, met a clear need for people with anorexia nervosa. Relevance to clinical practice: While further research is warranted mentoring support or recovered mentors, may play a potentially valuable role in supporting those in community settings.